PENGARUH LOKASI, HARGA, PROMOSI, DAN KUALITAS PELAYANANTERHADAP KEPUTUSAN MENGGUNAKAN OJEK ONLINE - Andrew Effendy Widjaja; Lilik indrawati (Jurnal Bisnis Terapan, 2018)
The advent of technology and increasingly stalled roads make the smart entrepreneurs in the field of technology to open a business. One of the businesses opened is an online transport business. In Indonesia, especially in Surabaya, the most popular transportation is taxibike online. One of the entrepreneurs desire is that his business can get a lot of consumers, of course it can not be separated from purchasing decisions that exist in the consumer. The online transport entrepreneur must know what is underlying in the consumer purchase decision. This study aims to analyze how much influence Location, Price, Promotion and Quality of Service to Decision in using Taxibike Online at students Catholic University Darma Cendika in Surabaya. Sampling method used is Purposive Sampling. The sample in this research is 75 students of Catholic University Darma Cendika, then analyzed the data obtained by using quantitative data analysis covering validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination (R2), and hypothesis testing through t test. Data that has met the validity test, reliability test and classical assumption test is processed using SPSS ver.16, so as to produce regression equation as follows :Y = 9,324 + 0,074 X1 + 0,157 X2 + 0,061 X3. Where is Purchase Decision variable (Y), Price variable (X1), Promotion variable (X2) and Service Quality variable (X3). Hypothesis testing using t test shows that the three independent variables namely Price (X1) with tcount 0,738, Promotion (X2) with tcount 1,848 and Service Quality (X3) with tcount 0,945 not influence to dependent variable of Purchase Decision (Y) because tcount < ttable ( 1,994).The Adjusted R Square number of 0.121 indicates that 12,1 percent of the Purchase Decision variable can be explained by the three independent variables in the regression equation, and have a very low level of relationship, while the remaining 87,9 percent is explained by other variables beyond the three variables used in this study.